Patterns and timing of recurrence in esophageal squamous cell carcinoma patients treated with neoadjuvant chemoradiotherapy plus esophagectomy - Yushi Nagaki (BMC, 2021)
Abstract Background Tumor regression grade (TRG) after neoadjuvant therapy is reportedly predictive of prognosis in esophageal cancer patients, as lack of a response to neoadjuvant therapy is associated with a poor prognosis. However, there is little information available on the timing and pattern of recurrence after esophagectomy for thoracic esophageal squamous cell carcinoma (TESCC) that takes into consideration TRG after neoadjuvant chemoradiotherapy (NACRT). Here, in an effort to gain insight into a treatment strategy that improves the prognosis of NACRT non-responders, we evaluated the patterns and timing of recurrence in TESCC patients, taking into consideration TRG after NACRT. Methods A total of 127 TESCC patients treated with NACRT and esophagectomy between 2009 and 2017 were enrolled in this observational cohort study. TRGs were assigned based on the proportion of residual tumor cells in the area (TRG1, ≥1/3 viable cancer cells; 2, < 1/3 viable cancer cells; 3, no viable cancer cells). We retrospectively investigated the timing and patterns of recurrence and the prognoses in TESCC patients, taking into consideration TRG after NACRT. Results The 127 participating TESCC patients were categorized as TRG1 (42 patients, 33%), TRG2 (56 patients, 44%) or TRG3 (29 patients, 23%). The locoregional recurrence rate was higher in TRG1 (36.4%) patients than combined TRG2–3 (7.4%) patients. Patients with TRG3 had better prognoses, though a few TRG3 patients experienced distant recurrence. There were no significant differences in median time to first recurrence or OS among patients with locoregional or distant recurrence. There was a trend toward better OS in TRG2–3 patients with recurrence than TRG1 patients with recurrence, but the difference was not significant. Conclusions NACRT non-responders (TRG1 patients) experienced higher locoregional recurrence rates and earlier recurrence with distant or locoregional metastasis. TRG appears to be useful for establishing a strategy for perioperative treatments to improve TESCC patient survival, especially among TRG1 patients. (303 words).